Relationship Educator Experiences of Couple Improvement and Group Dynamics in Relationship Education With Low-Income Couples. (April 2018) - Wheeler, Naomi J.; Harris, Shaywanna; Young, Mark E.
Relationship education (RE) interventions improve relationship quality and distress; yet, little is known about the origins of positive gains derived from RE. Couples identified benefits from the group format of RE; however, the perspective of facilitators is neglected. Therefore, the current investigation included two focus groups ( N = 9) with RE facilitators from one federal RE program for low-income couples. Five themes emerged from the phenomenological analysis including (a) therapeutic factors of groups, (b) participant attributes, (c) stress, (d) insight/awareness, and (e) program attributes . Applications of RE facilitator experiences, specifically group factors observed, may inform RE facilitator training, intervention, and implementation.